2019
DOI: 10.3171/2018.12.focus18589
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive mechanisms for stem cell transplant survival in spinal cord injury

Abstract: Spinal cord injury (SCI) has been associated with a dismal prognosis—recovery is not expected, and the most standard interventions have been temporizing measures that do little to mitigate the extent of damage. While advances in surgical and medical techniques have certainly improved this outlook, limitations in functional recovery continue to impede clinically significant improvements. These limitations are dependent on evolving immunological mechanisms that shape the cellular environment at the site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…TNF-α increases local expression of caspases, leading to apoptosis, and iNOS promotes the apoptosis of the damaged neuron. This process becomes inhibitory for the axonal regrowth over a prolonged period [40,41]. However, spontaneous regeneration of myelin sheaths often occurs following CNS demyelination, mainly by the differentiation of oligodendrocyte precursor cells (OPC) into myelinating OCs or SCs.…”
Section: Cns Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-α increases local expression of caspases, leading to apoptosis, and iNOS promotes the apoptosis of the damaged neuron. This process becomes inhibitory for the axonal regrowth over a prolonged period [40,41]. However, spontaneous regeneration of myelin sheaths often occurs following CNS demyelination, mainly by the differentiation of oligodendrocyte precursor cells (OPC) into myelinating OCs or SCs.…”
Section: Cns Injurymentioning
confidence: 99%
“…Sosa et al reviewed the neuroprotective effects and functional recovery after PNI and SCI in response to cyclosporine and tacrolimus, in 2005 [82]. Numerous preclinical studies have investigated the use of tacrolimus and cyclosporine in an allogeneic stem cell transplantation for treating SCI, as reviewed by Antonios et al in 2019 [41].…”
Section: Immunosuppression Following Pni and Scimentioning
confidence: 99%
“…On the other hand, administration of the immunosuppressant tacrolimus (FK506) can also promote peripheral nerve regeneration and functional recovery 11,12 . FK506 can prevent T‐cell proliferation 13 and inhibit T‐cell function by binding to FK‐binding proteins (FKBPs) 14 . It has been shown that FK506 can promote peripheral nerve regeneration through suppression of fibroblast proliferation, which is activated by inflammatory cytokines at the site of nerve repair, 11,15 and can exert a maximal effect on nerve regeneration when administered at a high dose (5 to 10 mg/kg/d) after nerve crush injury in rats 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the survival of transplanted MSCs is jeopardized by the unfavorable immune microenvironment of injured nerves, which substantially hampers the beneficial effect of MSCs on nerve repair 21–24 . It has been reported that the survival rate of MSCs can be increased by FK506 after spinal cord injury 14 . Concurrent administration of MSCs and FK506 was shown to be able to improve survival of allogeneic grafts 25 .…”
Section: Introductionmentioning
confidence: 99%
“…One effect is the migration of cells to the damaged tissue and differentiation into tissue-specific cell types, thus restoring the function of target tissues and organs. The other effect is the inhibition of local inflammation, apoptosis, and fibrosis; promotion of angiogenesis; and stimulation of regeneration and differentiation of resident tissue progenitor cells by secreting soluble growth and trophic factors [ 12 , 13 ]. Moreover, MSCs have several advantages, such as the ability to differentiate into multiple lineages, low immunogenicity, abundant sources, simplicity of preparation, and low tumorigenicity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%